Labour markets Performance and migration flows in Arab Mediterranean countries: determinants and effects. Volume 3: national backgroung papers Mashreg (Egypt, Palestine, Jordan, Lebanon, Syria) - Fargues, Philippe; Martín, Iván (Luxembourg, 2010)
"This study, which analyses the key labour market determinants of migration flows from selected Arab Mediterranean Countries (Algeria, Egypt, Jordan, Lebanon, Morocco, Syria, Tunisia and the Occupied Palestinian Territories) finds that employment in AMCs is a major challenge for the region – and for Europe – in the next 10 to 15 years. Immdiate action is needed because the status quo risks causing permanent damage to the development prospects of those countries. The AMCs' public policies are currently ill equipped to face the challenge. Labour migration remains a key feature of the labour markets in these countries – yet cannot by itself solve the labour market challenges there.